Avaliação da eficácia do Projeto de Extensão no Ensino da Língua Alemã: intercâmbio Alemanha e Brasil - Miranda, Mônica Mählmann Muniz (2023)
In Brazil, the German language is more widespread in the South and Southeast regions. Teaching in the other areas is still incipient compared to other languages, such as English and Spanish. However, since 2008, to expand the dissemination of the German language on all continents, the PASCH project has been developed – a partnership for the future. This project is funded by the Goethe-Institut (GI), which, since the 1960s, has entered a partnership with the Casa de Cultura Alemã (CCA), of the Federal University of Ceará (UFC). In Ceará, this project has been developed in Fortaleza in two partner public schools: Escola Estadual de Educação Profissional Paulo VI (EEEP Paulo VI) and Escola Estadual de Educação Profissional Juarez Távora (EEEP Juarez Távora) since 2010. Therefore, this work aims to evaluate the effectiveness of the PASCH project in the participating schools, comparing the goals established by the project and the results achieved by the students. To carry out the research, typified as descriptive, we used the structured questionnaire, which was applied to students who are part of the German course, in the year 2022, of the PASCH Project, which takes place at EEEP Juarez Távora and Paulo VI, both State Schools of Vocational Education. Data collection took place online through Google Forms, which is a perfect tool for anyone who is doing research and needs feedback. The collection was made by sending 165 questionnaires, with a return of a sample of 77 participants. Among the results of the research, the data show that the students believe that the small number of class hours negatively interferes with language learning. Other aspects that hinder the acquisition of German are the structure of the classrooms, the lack of material to study in the classroom, the lack of interest, and the lack of good didactics by the teachers. Still, the lack of playfulness to remove monotony in classes, and the lack of determination and focus on the part of the student body hinder the learning process. A factor that was relevant in the results of this research was the period of the Covid-19 pandemic, since the most significant incentive strategy for students to dedicate themselves to the course, which is the trip to Germany, could not be implemented so the practice of language study was carried out through the online modality during the pandemic period. It is concluded that the PASCH Project fulfilled its objectives, that is, it took the German language, as well as its culture, to the world, including Fortaleza, but the performance of the students could be better, considering the importance of learning. of a foreign language, which must be brought to society.